2012
DOI: 10.1111/j.1440-1746.2011.06933.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin G4 associated with number and distribution of extrapancreatic lesions in type 1 autoimmune pancreatitis patients

Abstract: Our findings indicated that serum IgG4 was useful in both the diagnosis of type 1 AIP and the detection of systemic EPL. Our finding may help the concept and diagnostic criteria of IgG4-related disease with type 1 AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…That is, patients with elevated serum IgG4 concentrations denote a large subset of patients with IgG4-RD whose disease is characterized by more extensive organ involvement, high inflammatory markers, low complement levels, and (possibly) greater refractoriness to treatment as compared with patients with normal IgG4 levels. [11][12][13][14] In a study of patients with autoimmune pancreatitis, Matsubayashi et al 11 reported a higher frequency of certain symptoms (eg, jaundice) and number of extrahepatic lesions together with a large size of pancreatic lesions in patients with higher IgG4 levels.…”
Section: Serum Igg4 Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…That is, patients with elevated serum IgG4 concentrations denote a large subset of patients with IgG4-RD whose disease is characterized by more extensive organ involvement, high inflammatory markers, low complement levels, and (possibly) greater refractoriness to treatment as compared with patients with normal IgG4 levels. [11][12][13][14] In a study of patients with autoimmune pancreatitis, Matsubayashi et al 11 reported a higher frequency of certain symptoms (eg, jaundice) and number of extrahepatic lesions together with a large size of pancreatic lesions in patients with higher IgG4 levels.…”
Section: Serum Igg4 Levelsmentioning
confidence: 98%
“…None of these features is pathognomonic of IgG4-RD, however, and even elevated IgG4 levels have been reported in a wide range of diseases (Table 3). 14,[66][67][68][69][70] In addition, limitations about its test characteristics preclude reliance on measurements of serum IgG4 levels for the purpose of diagnosis.…”
Section: Differential Diagnosismentioning
confidence: 98%
“…Firstly, there was inevitable heterogeneity in the meta-analysis of diagnostic accuracy due to the variability in design characteristics and the poor quality of reporting in the primary studies. The quality of the studies included in the meta-analysis was modest for our meta-analysis because ten studies were retrospective designed19232425262728293334, six studies were prospective designed111618303536, and seven studies did not report the study design291015173738. The QUADAS-2 tools for the methodological assessment indicated that other contributors to the potential heterogeneity across the studies result from the risk bias in patient selection due to the diagnosis of IgG4-RD on the basis of multiple criteria, as well as due to the detection method for serum IgG4 despite the clear cut-off value given in several studies2425262728.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IgG4-RD is a rare disorder with low incidence compared with other autoimmune disease, and the small sample sizes in previous studies focusing on the features of serum IgG4 level frequently led to a variable diagnostic accuracy of IgG4 in patients with IgG4-RD6915. Notably, IgG4-RD is a systemic fibro-inflammatory disease that has a similar pathogenesis and cardinal features in affected organs; however, it was rarely analysed as an extensive entity but rather an individual disorder focused on a single organ, especially the pancreas and salivary or lacrimal glands21116171819.…”
mentioning
confidence: 99%
“…For serum IgG4 levels, the sensitivity and specificity were 78.7% and 87.7%, respectively, which are not as high as the initial study by Hamano et al 26 , but are close to the reports by Ghazale et al 9 and other previous reports 10 11 12 . The differences in the diagnostic values of serum IgG4 for AIP could be attributed to differences in the patients enrolled in the studies, or differences in the disease activity of the cases selected 27 28 .…”
Section: Discussionmentioning
confidence: 99%